232k views
1 vote
What is the solution to this set of equations? Show your work.

y=5x−9

y=x^2−3x+7

1 Answer

5 votes

Answer:

(4, 11)

Explanation:

Given the 2 equations

y = 5x - 9 → (1)

y = x² - 3x + 7 → (2)

Substitute y = x² - 3x + 7 = 5x - 9 ( subtract 5x - 9 from both sides )

x² - 8x + 16 = 0 ← quadratic equation in standard form

(x - 4)² = 0 ← in factored form as a perfect square, so

x - 4 = 0 ⇒ x = 4

Substitute x = 4 into (1) for corresponding value of y

y = 20 - 9 = 11

Solution (x, y) → (4, 11)

User Zlopez
by
6.2k points